Polyesters and polyamides - Deopura, B. L. (Woodhead publishing in textiles, 2008)
Polyesters and polyamides remain the most used group of synthetic fibres. This authoritative book reviews methods of their production, ways of improving their functionality and their wide range of applications. The first part of the book describes raw materials and manufacturing processes, including environmental issues. Part two considers ways of improving the functionality of polyester and polyamide fibres, including blending, weaving, coloration and other finishing techniques as well as new techniques such as nanotechnology. The final part of the book reviews the range of uses of these important fibres, from apparel and sportswear to automotive, medical and civil engineering applications. With its distinguished editors and international team of contributors, Polyesters and polyamides is a standard reference for all those using this important group of fibres. Reviews the chemical and physical properties of each fibre and their manufactureAnalyses how the functionality of polyester and polyamides can be improvedProvides examples of how the fibres are used in applications.